Desigualdade socioespacial e o efeito-vizinhança em favelas de Belo Horizonte - Eduardo Marchetti Pereira Leao da Motta (2017)
This work explores the relationships between territory, segregation and neighborhood effect, with a focus on slums. These are considered places of poverty, vulnerability and social inequality in cities. They should be understood in their plurality and heterogeneity, as regards various factors such as access to basic services (electricity, water, sewage, garbage collection), access to public health and education, job opportunities, consumption, leisure and culture, as well as its history of occupation and treatment of public authorities. The location and level of socio-spatial integration of slums are part of a vicious circle that triggers opportunities or losses for its residents. The neighborhood effect represents this approach that focus the relational aspect between social groups physically close and studies its consequences. In Belo Horizonte, the Aglomerado Santa Lúcia and Vila Piratininga are situated in different positions in space and with particular surroundings: while the former is surrounded by noble neighborhoods of the South Zone of the capital, the latter is in the region of Barreiro, on the border with the municipality of Ibirité, with a similar environment regarding social vulnerability. Through interviews with the inhabitants of each slum, four main dimensions are investigated: 1) Vision about the community; 2) Public services; 3) Job and; 4) Consumption. The contrasts and similarities found can be explained from the approach of the neighborhood effect and the notion of spatial capital, considered as an asset to face situations of social vulnerability